State of the art of the 'right to special protection' for the case of the homeless in medellin: A critical socio-legal look (2019)
This article aims to build the state of the art of the 'right to special protection' of the homeless of Medellin from a critical socio-legal methodology, seeking to identify the theoretical trends, assumptions and contradictions of the studies of Medellin and their relationship with other inquiries at the national and international level. Thereon, it is possible to conclude that research on the issue is scarce and dominated by the official perspectives of public policies in Medellin while, contradictorily, in the other areas, a dominant role of the critical studies is defended, discovering the need to oppose a critical theory of the right to special protection for this social group in the city. In this sense, the issue is addressed in three parts: 1. Studies of homeless in Medellin, 2. Research in the national order, and 3. Research in the international order. © 2019, Universidad de Caldas.